The miR‐143/145 Cluster, a Novel Diagnostic Biomarker in Chondrosarcoma, Acts as a Tumor Suppressor and Directly Inhibits Fascin‐1. (10th March 2020) - Urdinez, Joaquin; Boro, Aleksandar; Mazumdar, Alekhya; Arlt, Matthias JE; Muff, Roman; Botter, Sander M; Bode‐Lesniewska, Beata; Fuchs, Bruno; Snedeker, Jess G; Gvozdenovic, Ana
ABSTRACT: Chondrosarcoma is the second most frequent bone sarcoma. Due to the inherent chemotherapy and radiotherapy resistance and absence of known therapeutic targets, clinical management is limited to surgical resection. Consequently, patients with advanced disease face a poor prognosis. Hence, elucidating regulatory networks governing chondrosarcoma pathogenesis is vital for development of effective therapeutic strategies. Here, miRNA and mRNA next generation sequencing of different subtypes of human chondrogenic tumors in combination with in silico bioinformatics tools were performed with the aim to identify key molecular factors. We identified miR‐143/145 cluster levels to inversely correlate with tumor grade. This deregulation was echoed in the miRNA plasma levels of patients and we provided the first evidence that circulating miR‐145 is a potential noninvasive diagnostic biomarker and can be valuable as an indicator to improve the currently challenging diagnosis of cartilaginous bone tumors. Additionally, artificial upregulation of both miRNAs impelled a potent tumor suppressor effect in vitro and in vivo in an orthotopic xenograft mouse model. A combined in silico/sequencing approach revealed FSCN1 as a direct target of miR‐143/145, and its depletion phenotypically resembled miR‐143/145 upregulation in vitro. Last, FSCN1 is a malignancy‐promoting factor associated with aggressive chondrosarcoma progression. Our findings underscore miR‐143/145/ FSCN1 as important players in chondrosarcoma and may potentially open new avenues for specific therapeutic intervention options. © 2020 American Society for Bone and Mineral Research.